ATMOSPHERIC AIR AS ONE OF THE PROBLEMS OF HUMAN LIFE SAFETY - Кобзаря, Елена; Котельникова, Лилия; Постаралкин, Владимир (Modern engineering and innovative technologies, 2017)
The paper deals with the problem of air pollution as a result of human activity; some results of analyzes of atmospheric air samples for the content of pollutants of various chemical classes in it are presented; The main sources of pollutant emissions int